Social times, reproduction and social inequality at work: contrasts and comparative perspectives between countries - Domínguez-Amorós, Màrius (2020)
If the focus is placed specifically on the problem of work and family, the daily life of people and their use of time are a main problem. This time is expressed in both freely available time, which is related to activities, and time of the productive and reproductive sphere. This chapter considers work in a broad sense and takes into account the sexual division of labour. Specifically, this chapter will explore transformations in time use and social inequality in unpaid work. For this purpose, a comparative analysis of time-use surveys will be used, analysing the time spent, and the time dedicated to household chores in Chile, Argentina, Uruguay and Spain. From an analytical viewpoint, the analysis will place social reproduction at the centre of the socio-economic system, showing that the economic crisis has affected women and men differently, and that in both Europe and Latin America the family pattern is being replaced by a dominant family model of a male provider and a double presence of women. The largescale incorporation of women into the labour market has emphasised the role that women assume in the domestic sphere perpetuating gender segregation in employment and in domestic and care work.